Pengaruh Pendapatan Asli Daerah, Ukuran Pemerintah Daerah, Opini Audit Terhadap Internet Financial Reporting Pemerintah Kota/Kabupaten Jawa Timur - Moehardiono, Irna Amelia; Yuliati, Anik (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This research aims to identify and examine the influence of local government revenue, size of local government, and audit opinion to local government Internet Financial Reporting. This research uses quantitative analysis techniques using secondary data retreived from local government financial reports in official website of the regency/city in East Java Province 2015-2019. Population used in this research were 38 city / district governments in East Java Province. Purposive sampling was used to collect sample data and obtained a sample of 23 districts/cities. This research used panel data regression analysis with software Eviews 9 to test three hypotheses. The results showed Â that local revenue, size of local government, and audit opinion had a simultaneous effect on local government Internet Financial Reporting practices. The partial test results showed that audit opinion affected Internet Financial Reporting of the local government. Meanwhile, local government revenue and size of local government does not affected Internet Financial Reporting.